The mystery of memory: in search of the past. (November 2013) - Paulson, Steve; Aciman, André; LeDoux, Joseph; Schacter, Daniel; Winter, Alison
Abstract : A universal fascination with how we remember, forget, and create false memories cuts across the arts and sciences, as do the questions of how and where memories are formed and preserved. Moderated by Steve Paulson, executive producer and host of To the Best of Our Knowledge, novelist and comparative literature professor André Aciman (City University of New York), neuroscientist Joseph LeDoux (New York University), psychologist Daniel Schacter (Harvard University), and historian of science and medicine Alison Winter (University of Chicago) discuss how memory impacts our perception of ourselves, the development of personality, and the ability to construct and reconstruct our past experience. The following is an edited transcript of the discussion that occurred November 14, 2012, 7:00–8:15 PM, at the New York Academy of Sciences in New York City.